Optimization of Mojokerto Police Samapta 4-Wheel Patrol in Preventing Cases of Theft with Weighting - Wigrhawan, Bagus Wira (Advances in Police Science Research Journal, 2024)
Basically, the Mojokerto Resort Police through the Samapta Unit has a big role in controlling and preventing cases of weighted theft by carrying out preventive efforts through 4-wheeled patrols. The aim of this research is to describe how 4-wheeled patrols are implemented, analyze the factors in carrying out 4-wheeled patrols and analyze optimizing the patrol activities of the Turjawali unit of the Mojokerto Police Samapta unit in implementing 4-Wheel patrols to prevent crimes of theft by weighting. The research was carried out using a qualitative research approach and case studies were the type of research used. The results of this research were that the 4-Wheel Patrol at the Mojokerto Police Department was running well in planning and organization, even though there was a lack of resources and a lack of leadership roles and a monitoring system. Supporting factors include the member's anthropology which makes the task easier, police patrols, community support, and other agencies. However, inhibiting factors include lack of resources, lack of concern from leadership, and the expertise of the perpetrators of the theft.